1956
DOI: 10.1002/zaac.19562840107
|View full text |Cite
|
Sign up to set email alerts
|

Über die Konstitution der sauren Sulfite. IV. Das „Zeitphänomen”︁ der sauren Sulfite

Abstract: Nachdem in einer früheren Mitteilung(1) gezeigt werden konnte, daß saure Sulfitlösungen, wie sie durch Auflösen von Disulfiten oder Halbneutralisieren von Schwefligsäurelösungen hergestellt werden, bei absolutem Luftausschluß auch im Licht keinerlei zeitlichen Veränderungen ihrer Konstitution unterliegen, wird an Hand von Raman‐Aufnahmen an belichteten und vor Licht geschützten, bei Gegenwart von Luftsauerstoff aufbewahrten, sauren Sulfitlösungen der Beweis geführt, daß das von K. SCHAEFER und Mitarbeitern(2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1956
1956
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Dimerisation of hydrogen sulfite has been investigated in aqueous solution by conductometry, 32 as well as IR, 12,33 UV [6][7][8][9][10]34 and Raman 10,11,[35][36][37][38] spectroscopic techniques. Table 1 summarises the reported values for the dimerisation constant, K D , in the literature.…”
Section: And 4 and References Therein)mentioning
confidence: 99%
“…Dimerisation of hydrogen sulfite has been investigated in aqueous solution by conductometry, 32 as well as IR, 12,33 UV [6][7][8][9][10]34 and Raman 10,11,[35][36][37][38] spectroscopic techniques. Table 1 summarises the reported values for the dimerisation constant, K D , in the literature.…”
Section: And 4 and References Therein)mentioning
confidence: 99%
“…40 The extensive vibrational spectroscopy studies conducted by Simon and Waldman revealed the presence of bisulte anion (HSO 3 À ), which resulted from the dissolution of SO 2 in water. [41][42][43][44][45] In addition, it has been proven that the existence of NH 3 in hydrated SO 2 clusters accelerates the production of HSO 3…”
Section: Introductionmentioning
confidence: 99%
“…The only other species detected in some cases were the HS04-and Sod--ions formed by slow oxidatioil of aqueous SO2, a reaction difficult to prevent during long exposures. Recently an extensive Raman study by Simon and Waldmann (15,16,17) revealed for the first time in these solutions some lines due to bisulphite ions, HSO3-, in very low concentration, as well as pyrosulphite ions, HS206-, pointing to the hitherto unsuspected equilibrium HS03-$ SO2…”
mentioning
confidence: 99%